The relationship between the parameters of microcirculation and the lung function in bronchial asthma in children - N. I. Lozko; N. G. Kolosova; N. A. Geppe; V. D. Denisova (Сеченовский вестник, 2018)
Among the chronic nonspeciﬁc lung diseases, bronchial asthma (BA) takes the leading place. BA in children is primarily diagnosed on the basis of clinical manifestations, methods of functional diagnosis, which allows you to verify the disease and assess the severity of the ﬂow. An important role in the pathogenesis of asthma is played by the microcirculation system, affecting the course and progression of the disease. Dysfunction of microcirculation system supports chronic inﬂammatory process, affecting the level of perfusion, metabolism and gas exchange. The study was carried out on the basis of the University Children's Clinical Hospital (pulmonology department) of the First Moscow State Medical University named after I.M. Sechenov Ministry of Health of Russia (Sechenovsky University). 100 children aged 6-17 years with asthma were examined. Based on the study of the nature of microcirculatory disorders by the LDF method in bronchial asthma in children with different severity of the disease, correlation links between microcirculation indices, clinical manifestations and external respiration function (spirometry and computer bronchophonography) in children have been revealed. The observed decrease in microcirculation during the exacerbation of asthma is short-term and insigniﬁcant in mild severity and is longer and more signiﬁcant with moderate BA, which supports a chronic inﬂammatory process in the bronchi. Correction of disorders of microcirculation is an important link in the therapeutic approach.